Restoration of Tajan River through ecological design approach - Kalantari, Fatemeh; Mohd Tahir, Osman; Golkar, Nazanin; Kalantari, Shahaboddin (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Rivers are one of the main natural landscape element in urban areas. The ecosystem of the Riverfront is important as well as the ecosystem of the Rivers. However, research has shown that the current urban river development and riverfront maintenance projects has neglected regarding to the importance of organisms and urban ecosystem .Recent studies on the Tajar River in Iran are illustrated that ecological policies and strategies have not been succeeded in different aspects. Therefore, restoration of the Tajan River is not considered as a main issue for ecological design. The aim of this paper is identification of ecological issues of the Tajan River. Then, some ecological design approaches are presented and feasibility of the approaches are investigated in this paper. A qualitative method is proposed which includes interview and observation method. Based on above, ecological approaches and suggestions are recommended to habitation the health of river ecosystems. The results are indicated that application of the proposed approaches may effect on the ecosystem balance and ecological improvement of Tajan River.